Analisis Kelayakan Usaha dan Nilai Tambah Produk Keripik Tempe Sagu Wortel “CARO” pada UMKM Benarasa Nusantara Kecamatan Cikarang Barat Kabupaten Bekasi - Muharam, Muharam; Mahatmayana, I Ketut Manu; Margaretha, Juliana (Peneliti.net, 2025)
The Benarasa Nusantara Micro, Small and Medium Enterprises (MSME) is one of the business that does agroindustry activities with its innovative product, 'CARO' Carrot Sago Tempe Chips. This study’s purpose are analyzing business feasibility and added value from the 'CARO' Carrot Sago Tempe Chips production process. This study was conducted using a quantitative research method with three respondents consisting of the Benarasa Nusantara MSME owner and two labours there are a labour from the family and a labour from out the family. Data analysis was carried out using the R/C Ratio Analysis and the Hayami Method. The results of this study are the business is declared feasible with an R/C ratio of 1,73 and the added value earned is Rp. 177.600,00/kg with a value added ratio of 67,66%.